2019
DOI: 10.1515/nleng-2017-0133
|View full text |Cite
|
Sign up to set email alerts
|

Postbuckling behavior of functionally graded CNT-reinforced nanocomposite plate with interphase effect

Abstract: The present paper is aimed to study the buckling and postbuckling response of functionally graded carbon nanotube (FG-CNT)- magnesium (Mg) nanocomposite plate with interphase effect. Interphase zone is characterized by employing a cohesive zone model for its elastic modulus and thickness. An equivalent solid fiber (ESF) of CNT and interphase is modeled and dispersed into the matrix material by utilizing random sequential adsorption (RSA) technique. The effective elastic properties of the nanocomposite are comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 71 publications
0
4
0
Order By: Relevance
“…They found that the bending performance of polymer matrix composite significantly improved by adding a small amount of graphene platelets. Srivastava and Kumar [26] investigated the postbuckling response of the graphene-sheet-reinforced plate comprising the effect of van der Waals bonding amongst the graphene sheet and matrix. By using the FEM-based homogenization technique, the effective elastic constants of the nanocomposite were evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…They found that the bending performance of polymer matrix composite significantly improved by adding a small amount of graphene platelets. Srivastava and Kumar [26] investigated the postbuckling response of the graphene-sheet-reinforced plate comprising the effect of van der Waals bonding amongst the graphene sheet and matrix. By using the FEM-based homogenization technique, the effective elastic constants of the nanocomposite were evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…Nanotechnology was applied in several research directions, and materials with different components and nanostructures were also developed to fulfill different requirements [1][2][3][4][5]. As a kind of nanomaterials, nanofibers prepared by organic or inorganic materials through the method of electrospinning were widely researched due to their advantages such as high porosity, specific surface area, and lightweight [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Unlike most nanomaterials, whose mechanical properties are homogeneous in macroscale [12], functionally graded materials (FGMs), first applied in aerospace structures, are deliberately manufactured to have mechanical properties with continuous spatial variations [13,14]. Recently, the concept of FGM has been introduced into the carbon nanotube-reinforced composites and some nonlinear mechanical characteristics were studied [15,16]. Nowadays, FGMs are applied widely in various structures as members or coatings [17].…”
Section: Introductionmentioning
confidence: 99%